Effects of Different Swimming Intensities on the Bone Properties of the Tibia and Femur of Wistar Rats in which Knee Rheumatoid Arthritis was Induced - Mioto, Alline Mardegan [UNESP]; Castoldi, Robson Chacon [UNESP]; Trindade Camargo, Regina Celi [UNESP]; Garcia, Thiago Alves; Reis, Daniel Fernando dos; Tamura Ozaki, Guilherme Akio; Trevisan, Iara Buriola [UNESP]; Pereira Ribeiro, Rodrigo Metzker; Silva Camargo Filho, Jose Carlos [UNESP] (Soc Chilena Anatomia, 2020)
Rheumatoid arthritis (RA) is a disease triggered by environmental and genetic factors. Research suggests that physical exercise has benefits such as delaying functional disability. In vivo studies using experimental models of arthritis can provide useful information about these benefits. to analyze the effects that different intensities of aquatic physical exercise have on the proprieties of the bones in induced arthritis in knees of Wistar rats. Male Wistar adults rats (n=20) were divided into 5 groups: Group Control Arthritis (GCA) n=4, Group control Placebo (GCP) n=4, Group Low Physical Activity (GB) n=4, Group Moderate Physical Activity (GM) n=4 and Group Intense Physical Activity (GI) n=4. The physical activity groups got an intra-articular injection of Zyrnosam on the right knee; the GCA received saline solution in the right knee; the GCP was submitted to the stress of the needle. The animals were submitted to aquatic activity for 30 minutes, 4 times a week for 5 weeks, and the intensity of the exercise was determined by a weight placed on their back: GB=1 %, GM=5 %, GI=15 % of their body weight. It was observed that the group GB, and the groups that did not exercise GCA and GCP, gained more weight compared to the group GM. In relation to the bone mineral content of the tibia, there was a decrease in the GM group when compared to the GCP group, whereas in the tibial bone mineral density there was a decrease in the GM group compared to the GCP, GCA, GB. As for the area of the femur, the GI group presented an increase of it compared to the GB and GM groups. It is concluded that the high intensity exercises promote better results in bone properties.
Keywords: Rheumatoid arthritis; Physical exercise; Wistar Rats; Arthritis induced in rats